The microbiome related to carbon and nitrogen cycling in pure and mixed Eucalyptus grandis and Acacia mangium plantations - Pereira, Arthur Prudêncio de Araujo (2018)
The introduction of N2-fixing trees in mixed forest systems is a recent strategy that can reduce the use of external inputs and increase the Eucalyptus plantations sustainability. In these systems, there is a strong interconnection between the trees, which occurs through a complex network of interactions between microorganisms, above and belowground. These interactions result in innumerable biological functions and ecosystem services, which are essential for soil and plant health. Moreover, the result of the Eucalyptus-microbiome-Acacia interaction has been pointed out as essential in achieving higher Eucalyptus productivity indexes in mixed systems. Our aim was to explore the dynamics of microbiome related to nutrient cycling in pure and mixed Eucalyptus grandis and Acacia mangium plantations. Specifically, our efforts were focused on the microbiome benefits to the biological functions improvement in commercial Eucalyptus plantations driving by Acacia introduction in the system. We also give details regarding as the knowledge of the microbiome diversity, composition and functions can help us to understand their close relationship with carbon (C) and nitrogen (N) cycling in soil and litter layers. We believe that holistic approaches in which we can explore the biological interactions in systems using plants of high ecological value (Acacia) and high economic value (Eucalyptus) will be inevitable in the near future. If we learn how to manipulate important processes mediated by the microbiome involved in these interactions, we will take an important step to overcome the current resource constraints, combining increased productivity with the ecological intensification of forest plantations and the environmental sustainability.